INTEGRATED ROLE MODEL PENGOLAHAN SUSU MENJADI KEJU DENGAN APLIKASI PERHITUNGAN PRODUKSI - Zakijah Irfin; Nurul Hidayatinnisa; Rosita Dwi Chrisnandari; Ulla Delfana Rosiani; Sri Rulianah (Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this community service is to integrate a zero-waste model for processing milk into cheese with a production calculation application at KU Mustarika Jaya Makmur Ngantang. This project aims to address several key issues faced by the cooperative, such as unstandardized milk quality, lack of product diversification, and insufficient economic analysis of dairy products. By implementing supply chain management practices, conducting comprehensive training sessions, and developing a digital application for production calculations, the project seeks to enhance the cooperative's operational efficiency and product quality. The results of the project demonstrate a significant improvement in the cooperative members' knowledge and skills in supply chain management, cheese production techniques, and economic analysis. The integration of a zero-waste model has led to more efficient use of resources and reduced waste, contributing to environmental sustainability. The production calculation application has provided the cooperative with valuable insights into cost management and profitability, facilitating more informed business decisions. Overall, this community service initiative has successfully enhanced the operational, leading to increased productivity, better product quality, and improved economic outcomes for the cooperative members.